Aeroacoustic Attenuation Performance of a Helmholtz Resonator with a Rigid Baffle Implemented in the Presence of a Grazing Flow. (19th April 2020) - Guan, Di; Zhao, Dan; Ren, Zhaoxin
Abstract : To broaden its' effective frequency range and to improve its transmission loss performance, a modified design of a Helmholtz resonator is proposed and evaluated by implementing a rigid baffle in its cavity. Comparison is then made between the proposed design and the conventional one by considering a rectangular duct with the resonator implemented in the presence of a mean grazing flow. For this, a linearized 2D Navier-Stokes model in frequency domain is developed. After validated by benchmarking with the available experimental data and our experimental measurements, the model is used to evaluate the effects of (1) the width L p of the rigid baffle, (2) its implementation location/height H g, (3) its implementation configurations (i.e., attached to the left sidewall or right sidewall), (4) the grazing mean flow M u (Mach number), and (5) the neck shape on a noise damping effect. It is shown that as the rigid baffle is attached in the 2 different configurations, the resonant frequencies and the maximum transmission losses cannot be predicted by using the classical theoretical formulation ω 2 = c 2 S / V L eff, especially as the grazing Mach number M u is greater than 0.07, i.e., M u > 0.07 . In addition, there is an optimum grazing flow Mach number corresponding to the maximum transmission loss peak, as the width L p is less than half of the cavity width D r, i.e., L p / D r ≤ 0.5 . As the rigid plate width is increased to L p / D r = 0.75, one additional transmission loss peak at approximately 400 Hz is produced. The generation of the 12 dB transmission loss peak at 400 Hz is shown to attribute to the sound and structure interaction. Finally, varying the neck shape from the conventional one to an arc one leads to the dominant resonant frequency being increased by approximately 20% and so the secondary transmission loss peak by 2-5 dB. The present work proposes and systematically studies an improved design of a Helmholtz resonator with an additional transmission loss peak at a high frequency, besides the dominant peak at a low frequency.